2000
DOI: 10.1111/0022-4537.00177
|View full text |Cite
|
Sign up to set email alerts
|

New Ways of Thinking about Environmentalism: Elaborating on Gender Differences in Environmentalism

Abstract: A review of recent research (1988 to 1998) on gender differences in environmental attitudes and behaviors found that, contrary to past inconsistencies, a clearer picture has emerged: Women report stronger environmental attitudes and behaviors than men. Additional evidence of gender differences in environmental attitudes and behaviors was also supported across age (Study 1) and across 14 countries (Study 2). As a single variable, the effect of gender on proenvironmental behavior was consistently stronger than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

120
801
23
51

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,321 publications
(1,062 citation statements)
references
References 40 publications
120
801
23
51
Order By: Relevance
“…Meta-regression 22 tested explanations for this variation. We included three country-level predictors on theoretical grounds: (a) climate change contributions (greenhouse gas emissions and renewable energy) 23 , indexing responsibility/culpability for climate change; (b) country wealth (GDP per capita), which has been associated with pro-environmental behavior 24,25 ; and (c) the proportion of females in each sample, as women are typically more pro-environmental 3,26,27 . The basic correlations for student samples were used to maximize the number of countries analyzed.…”
mentioning
confidence: 99%
“…Meta-regression 22 tested explanations for this variation. We included three country-level predictors on theoretical grounds: (a) climate change contributions (greenhouse gas emissions and renewable energy) 23 , indexing responsibility/culpability for climate change; (b) country wealth (GDP per capita), which has been associated with pro-environmental behavior 24,25 ; and (c) the proportion of females in each sample, as women are typically more pro-environmental 3,26,27 . The basic correlations for student samples were used to maximize the number of countries analyzed.…”
mentioning
confidence: 99%
“…Gender has previously been known to play a role regarding environmental concern, and may therefore be expected to affect attitudes towards renewables. In general, surveys have demonstrated fairly consistent results that women are more environmentally oriented than men (Dietz, Stern, and Guagnano 1998;Zelezny, Chua, and Aldrich 2000;Tranter 2011). …”
Section: Socio-demographic Variablesmentioning
confidence: 93%
“…Thus, it is interesting to investigate if hope concerning climate change is related to a teacher approach that allows students to discuss different pathways to sustainable development. Finally, since earlier studies have indicated that there are gender differences when it comes to both coping (Eschenbeck, Kohlman, & Lohaus, 2007) and environmental engagement (Torbjörnsson, Karlberg, & Molin, 2011;Zelezny, Chua, & Aldrich, 2000), it is also of interest to find out if differences exist between boys and girls when it comes to the two dimensions of hope.…”
Section: The Future Dimension In Esd and Pathways To Sustainable Devementioning
confidence: 99%